(untitled) (Latakia University Journal -Engineering Sciences Series, 2018)
تواجه التجمعات الحضرية والمدن الكبرى آثار التخطيط المشجع للزحف العمراني الذي دعم انتشار استخدام السيارات الخاصة، والذي دفع المخططين والباحثين حول العالم إلىتبني اتجاهات تنمية عمرانية جديدة تضمنت إعادة النظر في العلاقة التي تربط بين أنظمة النقل والتنمية العمرانية، بناءً على ذلك يناقش البحث أنظمة النقل كعامل موجه للتنمية العمرانية حسب هذه الاتجاهات ويدرس إمكانيات أنظمة النقل متعدد الوسائط وركائز استراتيجية التطبيق بهدف تحديد الفرص الموجودة في مدينة دمشق كإحدى المدن الكبرى التي لا تزال تواجه آثار التخطيط المركزي والانتشار المبعثر وتوسع النسج العمرانية الموجهة للمركبات، كما يطرح استراتيجية التطبيق الممكنة، ويخلص البحث إلى مجموعة نتائج وتوصيات توضح أهمية تبني هذه الاستراتيجية لإدارة نمو عمراني أكثر توازناً، وحماية المناطق الطبيعية وتنمية مجتمعات عمرانية مستدامة اقتصادياً وبيئياً واجتماعياً. As megacities and urban communities experiencing the effects of urban sprawl auto oriented planning, that emphasized widespread use of private cars, planners and researchers around the world adopted new urban development trends included re-evaluating the relationship between transportation systems and urban development.Therefore, the research discuses transportation systems as urban development orient factor according to the new trends, and multi-modal transportation systems capabilities, and the implementation strategy tools to define the existing opportunities in Damascus city as one of the megacities that still facing the effects of central planning,dispersed sprawl and auto oriented tissues expansion.The research also poses a possible applicable strategy, and concludes with set of results and recommendations shows the importance of applying this strategy to manage more balanced urban growth, protect natural areas, and economically, environmentally and socially sustainable development of urban communities.